In vitro Antitrichomonas Activity of Allium Hirtifloium (Persian Shallot) in Comparison with Metronidazole - M Taran; M Rezaeian; M Izaddoost (Tehran University of Medical Sciences, 2006)
Trichomonas vaginalis infection is a sexually transmitted infection causing vaginitis and acute inflammatory disease of the genital mucosa. Although Metronidazole resistance in T. vaginalis is well documented, The only drug approved for the treatment of trichomoniasis in some countries is metronidazole. Genus Allium plants including garlic; shallot and onion have had an important medicinal role for centuries. Some study have proven antibacterial, antifungal, antiviral, antiprotozoal and antihelmintic properties of genus Allium plants. at first PSHE and PSDE ( persian shallot hydroalcoholic and dichlromethanic extract) was prepared in ethanol/water (50:50) and dichlromethane respectively at cool temperature (10ºC). genus Allium plants extracts were shown to decrease the oxygen uptake, reduce the growth of the organism, inhibit the synthesis of lipids, proteins and nucleic acids and damage membranes. In this study the Minimal Inhibitory Concentrations (MICs) of PSHE, PSDE and metronidazole respectively were 10, 5 and 2µg/ml. Persian shallot inhibited growth of T. vaginalis at low concentrations and in short times, therefore this plant have some antitrichomonas components (including allicin, ajoene and other organosulfides) that antimicrobial properties of these was proven.